PUBLIC-UTILITY DEPRECIATION IN ITS RELATION TO THE RATE BASE. - Krebs, W. S. (The Accounting Review, 1939)
Abstract This article focuses on the relation between depreciation and rate base. Depreciation of capital assets and depreciation accounting in public utilities have long been the source of much controversy between the utilities and the state. The problem has been complicated by the unwillingness of some to recognize depreciation at all and by the insistence on the part of others that reproduction cost should be the fundamental element in the rate base determination, and in the decision made relative to the amount of the depreciation charge. It has been still further complicated by using one amount of depreciation for total charges to operating expenses and another, a smaller amount, or none at all, for deductions in calculating the rate base. A generalized statement of sound procedure has been hard to formulate, because the application to specific companies is so varied. One approach to the problem of understanding the relationship between depreciation and the rate base, consists of presenting thirteen examples which may be looked upon as thirteen cases handed down by a commission and which call for adjudication. Some of these examples represent undepreciated rate bases, some depreciated rate bases and some bases for which no names are given. Some follow the retirement method, some the depreciation method and some both the retirement and the depreciation methods. By no means are all of these examples equally satisfactory or typical. In fact some are quite the reverse.